The Role of Motivation In Mediating The Influence of Human Relations and Discipline on Employee Performance At The Directorate of Port Ministry of Transportation - Abdul Hakim Kamil; Tiara puspa; Achmad Fauzi (Publikasi Indonesia, 2022)
The purpose of the study was: